Modal Sosial Yayasan Anak & Ibu Hamil: Analisis Sosiologis di Yayasan Rumah Bayi Bali - Guswah, Yasmin; Suryani, Ni Gusti Ayu Putu; Aditya, I Gusti Ngurah Agung Krisna (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
ABSTRACT This study analyzes the role of social capital in fulfilling the rights of abandoned children and pregnant women at Yayasan Rumah Bayi Bali, using Robert Putnam's social capital theory. The foundation plays a crucial role in providing protection and support for pregnant women experiencing out-of-wedlock pregnancies, as well as for children in need of care. The focus of this research is to examine how the elements of social capital, trust, norms, and networks, contribute to the foundation’s operations. This study employs a qualitative approach with a descriptive-explanatory method. The findings indicate that trust is a key element in the relationships between the foundation and the community, government, and pregnant women. The foundation builds trust through transparency, legal certainty, and open communication with the women they support. In terms of norms, the foundation enforces strict regulations regarding the acceptance of pregnant women and ensures that the children under their care have a clear maternal identity. Meanwhile, the foundation strengthens its networks through relationships with staff, social media utilization, and the connections of the foundation’s owner in the IT business sector and his experience as a guide, which also contributes to the financial sustainability of Yayasan Rumah Bayi Bali . Keywords: Foundation, Social Capital, Trust, Norms, Networks